Effect of coronavirus disease 2019 on diagnosis and treatment of hepatocellular carcinoma: a systematic review - Afrooz Mazidimoradi; Samane Sabet Birjandi; Hamid Salehiniya (Open Exploration Publishing Inc., 2023)
Aim: Changes in strategies in the coronavirus disease 2019 (COVID-19) crisis and the imposing of restrictions have isolated many vulnerable patients including those with hepatocellular carcinoma (HCC) from routine medical care. This study investigated how the COVID-19 pandemic is affecting the diagnosis and treatment of HCC. Methods: An extensive search was conducted in the PubMed, Scopus, and Web of Science databases by using the appropriate keywords: COVID-19, hepatocellular carcinoma, hepatocellular cancer, and MeSH. Studies in English related to the purpose of the study were included in the analysis, and review studies, case reports, letters to editors, comments, and reports were excluded. The quality of the studies was assessed by the "Adapted Newcastle-Ottawa Quality Assessment Scales" checklist. The Endnote X7 software has been used for managing items. Results: The final qualitative analysis consisted of 27 articles. During the COVID-19 crisis, HCC diagnosis decreased from 20% to 34.13% compared to pre-crisis. The impact of the COVID-19 pandemic on HCC treatment encompasses a wide range of aspects. Generally, delays in treatment for patients with HCC ranged from more than one month for 21.5% of patients in France, to two months for 26% of patients in Italy, up to 30% in Austria, and 66.7% in Asia-Pacific countries. Conclusions: According to the findings, developing and implementing appropriate diagnostic and therapeutic strategies and developing low-cost and high-precision screening programs among high-risk populations seem to be effective in reducing the impact of the COVID-19 pandemic on HCC management.